Urbanization impacts on greenhouse gas (GHG) emissions of the water infrastructure in China: Trade-offs among sustainable development goals (SDGs). (20th September 2019) - Zhang, Qian; Liu, Shuming; Wang, Tao; Dai, Xiaohu; Baninla, Yvette; Nakatani, Jun; Moriguchi, Yuichi
Abstract: The lasting urbanization in China has moved to the 'new-normal' stage, in which rural-to-urban migration, inefficiency in land use, and insufficient public services are the key challenges. To prevent urban sprawl, the compact city design intensively focuses on the improvement of housing and transport services to increase urban accessibility, vitality and diversity. Clean water and sanitation is also an essential function of cities, but the impacts from China's future urbanization on unheeded water infrastructure were sparsely estimated, especially from a perspective of urban metabolism. This study examines the complex response in the water sector to Chinese urban policies taking resource efficiency into account GHG emissions. A hypothetical grid-city model was developed to connect technical parameters in urban water infrastructure systems to the socio-economic changes, such as population growth, housing blocks, and water end-use. The results show that the pipeline construction dominates material use and locks in significant GHG emissions in the water sector. The most efficient urbanization scenario can reduce 60% of GHG emissions from the water infrastructure, compared to the case of urban sprawl with residency restriction in large cities. A trade-off in scenarios was observed between the optimization for mega-cities and the optimization for the whole of China regarding the additional energy consumption for pumping in the water sector. As empirical evidence of China, this study shows the conflict between SDG 6 (Clean water and sanitation) and SDG 13 (Climate action) in the urban water sector can be largely alleviated by an efficiency-focused urban policy complying with SDG 11 (Sustainable cities and communities). A loosen migration regulation and compact urban planning in the medium- and large-sized cities are recommended, along with advanced water technologies to promote sustainable urban water management in China. Highlights: We revealed the complex response in the urban water systems to GHG emissions for China. A generalized model was designed to connect strategic planning of water systems to urban systems. Future scenarios evaluate the impacts of urban policies, water technologies, and carbon intensities. The conflict between SDG 6 and SDG 13 can be alleviated by the compact and efficient urban planning.